PROFIL FITOKIMIA DAN UJI SITOTOKSIK EKSTRAK ETANOL TUMBUHAN Zanthoxylum acanthopodium DC (ANDALIMAN) MENGGUNAKAN METODE BSLT - Liis Panggabean; Nurhamidah Nurhamidah; Dewi Handayani (University of Bengkulu, 2020)
The purpose of this study was to determine the phytochemical profile of Zanthoxylum acanthopodium DC plant (Andaliman) and to know the extract part of plant ethanol Z acanthopodium DC as the best anticancer agent. Root basal samples, stem bark, leaves and fruit Z acanthopodium DC as much as 3 Kg, then dried up and smoothed. Fine samples of root, bark, leaves and fruit of Z acanthopodium DC were each weighed 450 gr and each sample was extracted using 5 L ethanol solvent. Root extract, bark, leaves and fruit Z anthoxylum acanthopodium DC obtained from extraction weighed as much as 1 g, then each of them in concentrations of 10, 100, and 1000 ppm. Cytotoxic tested using BSLT method with shrimp larvae of 10 tail, then determined LC50 by using relationship between probit and log of concentration. Each sample of fine roots, bark, leaves and fruit Z acanthropodium DC were weighed 3 grams. Then press the phytochemical profile. Phytochemical profile test results of each sample of acanthopodium DC Z showed the presence of alkaloids, flavonoids, tannins, terpenoids and saponins. The largest alkaloid content is found on the skin of stems and roots (++) with Papaya leaf comparison, the largest flavonoid content of bark (++) skin with peach flower compound, tannin leaf and tanug (+++) seedlings with Avocado seed comparator, and the largest Kandugan saponin on bark (+++) with the comparative Starfruit Wuluh. In the cytotoxic test results, each leaf extract of stem, leaves, roots and Z acanthopodium DC fruit has potential as an anticancer agent because the liberating LC50 in each sample is in the range 30-1000 ppm. The extract part of the stem bark has the greatest potential as an anticancer compared to fruits, leaves and roots. Because bark leaf extract has LC50 so that 57,677 ppm compared to root of 65,313 ppm, leaves of 77, 983 ppm, and fruit of 191,426 ppm. Usually root samples, stem bark, leaves and fruit Z acanthopodium DC can be used as an anticancer because of the content of flavonoids, saponins, alkaloids, tannins, and terpenoids.